Urban Development of Užice in the 18th and Early 19th Century - Kuzović, Duško R. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
During the first half of the 19th century in Užice began a gradual strengthening of the Christian part of the settlement, and after a series of conflicts Muslim part of the city gradually decreased, until it eventually disappeared in 1863. After liberation oriental city continued to exist with all principles and divisions until the adoption of the new plan in 1863. Only reliable geodetic testimony about this city is the current state of the central part of the town for the purposes of the Regulatory Plan, which was recorded by an engineer named Emanuel Schefel in 1863. With that plan for the reconstruction of the city, all traces of oriental in urban fabric of Užice will be erased. City’s population wanted to remove oriental period of the development as fast as possible, but it was not easily realized. After the reconstruction of streets, blocks, new rules of construction on the plot, new materials, new forms and so, ancient Oriental city is preserved in the place names of certain parts of the village, also called old mahala, which are used to this day (Rosulje, Pašinovac, Megdan, Međaj, Lipa, Carina, Terazije, Kostica etc.). It can even be said that the laws of the former mahala were authoritative in determining the neighborhood unit rather than the streets, until the end of the 20th century. The functional layout of the village of oriental city has retained to this day: the center is the site of the bazaar and the residential blocks are arranged in places of the mahalas. Tracks from oriental city streets during reconstruction are largely retained, except for being corrected and enlarged. Such an act mostly conditioned the arrangement of the plots purchased by the populace who left town in 1863. Their position influenced the shape of the new city blocks dragging their impact even to the shape of plots, the basics of the facilities and the organization of the apartments. The modern method of construction of the facilities (Neighborhood assistance) and approach to construction (as resources permit, during several years) indicate that the oriental city provides its long roots to the present day. Weather the traces are deleted or modified and fitted in a modern way of life, Oriental city in modern Užice still exists.